2016
DOI: 10.1083/jcb.201508080
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of FAK and Src adhesion signaling occurs independently of adhesion complex composition

Abstract: Adhesion signaling of integrin adhesion complexes (IACs) is sensitive to inhibition of key IAC kinases (FAK and/or Src), but IAC composition is not, demonstrating a separation between signaling and structural contributions of IAC components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 94 publications
3
75
0
Order By: Relevance
“…6E). In accordance with previously published results, FAK inhibition reduced cell velocity (Horton et al, 2016). FAK inhibition also blocked the increased migration seen after LIPUS stimulation in MC3T3 cells, suggesting that this is a universal mechanism (Fig.…”
Section: I997asupporting
confidence: 80%
See 1 more Smart Citation
“…6E). In accordance with previously published results, FAK inhibition reduced cell velocity (Horton et al, 2016). FAK inhibition also blocked the increased migration seen after LIPUS stimulation in MC3T3 cells, suggesting that this is a universal mechanism (Fig.…”
Section: I997asupporting
confidence: 80%
“…6B). We and others have recently shown that pretreatment with 3 µM FAKi for 1 h reduces tyrosine phosphorylation at FAs in NIH3T3 and HFF cells, without affecting the molecular composition of FAs or vinculin turnover (Horton et al, 2016;Stutchbury et al, 2017).…”
Section: I997amentioning
confidence: 99%
“…Regulation of adhesion complexes by LAR is independent of FAK activity FAK and Src are non-receptor tyrosine kinases frequently linked to adhesion complex dynamics, cell adhesion and cell migration (Mitra and Schlaepfer, 2006), although recent data also report that adhesion complex composition is unaffected when Src and FAK are inhibited (Horton et al, 2016). Tyr 118 of paxillin is a known FAK substrate (Bellis et al, 1995), and we tested whether activation of FAK was affected in the absence of LAR activity.…”
Section: Resultsmentioning
confidence: 99%
“…extensively characterized and lead to a strong inhibition of FAK and paxillin phosphorylation in the FA (Horton et al, 2016, Fig. S4A).…”
Section: Fak and Paxillin Phosphorylation In Mechanotransductionmentioning
confidence: 99%
“…NIH3T3 cells were trypsinized and suspended in 2 ml of supplemented DMEM containing 3 µM FAKi+3 µM Srci+50 µM Y-27632, or an equivalent volume of DMSO for 1 h. These concentrations and treatment times are sufficient for maximal FAK and Src inhibition (Horton et al, 2016). Cells were plated on FN-coated coverslips for 4 h prior to fixation and staining.…”
Section: Y-27632 Experimentsmentioning
confidence: 99%